No difference in the maximum frost hardiness of different pedunculate oak populations in Finland - Repo, Tapani; Volanen, Virva; Pulkkinen, Pertti (Suomen metsätieteellinen seura, 2022)
The natural northern distribution limit for pedunculate oak (Quercus robur L.) is in southern Finland. We hypothesized that the maximum frost hardiness (FHmax) in the winter limited the cultivation of oaks in northern latitudes. We tested the hypothesis with controlled freezing tests in midwinter. The acorns for the experiment were collected from the four main oak populations in southernmost Finland. The seedlings were raised in the nursery, frost hardened in field conditions, and then moved to a growth chamber at –2 °C on two occasions in winter and tested for FHmax in controlled freezing tests. Frost hardiness was assessed by differential thermal analysis (DTA) based on the low temperature exotherm (LTE) and relative electrolyte leakage (REL) of the stem, and visual damage scoring (VD) of the buds and stem. The initiation and peak of the LTE took place at an average of –41 °C and –43 °C respectively, without differences among the populations. The variation in the initiation and peak of the LTE was high, ranging from –34.6 °C to –45.5 °C and from –37.1 °C to –46.9 °C respectively. According to the REL method, the frost hardiness of the populations ranged from –44.0 °C to –46.4 °C in February and from –40.6 °C to –41.6 °C in March, without significant differences among the populations. According to VD, the bud was the least frost hardy organ, with FH between –19 °C and –33 °C, depending on population and assessment time. We conclude that the maximum hardiness may set the limit for the distribution of pedunculate oak northwards, but the high within-population variation offers potential to breed more frost hardy genotypes.
Keywords: frost hardiness; pedunculate oak; winter hardiness; differential thermal analysis; electrolyte leakage; climate acclimation; climate adaptation; species distribution; frost hardiness; pedunculate oak; winter hardiness; differential thermal analysis; electrolyte leakage; climate acclimation; climate adaptation; species distribution